2005
DOI: 10.1111/j.1945-5100.2005.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Re-examining the role of chondrules in producing the elemental fractionations in chondrites

Abstract: Abstract-The matrices of all primitive chondrites contain presolar materials (circumstellar grains and interstellar organics) in roughly CI abundances, suggesting that all chondrites accreted matrix that is dominated by a CI-like component. The matrix-normalized abundances of the more volatile elements (condensation temperatures <750-800 K) in carbonaceous and ordinary chondrites are also at or slightly above CI levels. The modest excesses may be due to low levels of these elements in chondrules and associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 124 publications
(234 reference statements)
6
55
0
Order By: Relevance
“…2 the H/C ratio is plotted vs. the matrix-normalized abundance of IOM C in the bulk meteorites. Alexander et al (1998) and Alexander (2005b) observed that, like presolar grains (Huss and Lewis, 1995), the matrix-normalized IOM abundances in the most primitive chondrites are similar. Thus, the matrix-normalization makes it possible to compare the different meteorite classes and to look for trends that might be common to all.…”
Section: Intra-and Inter-class Variationsmentioning
confidence: 88%
See 3 more Smart Citations
“…2 the H/C ratio is plotted vs. the matrix-normalized abundance of IOM C in the bulk meteorites. Alexander et al (1998) and Alexander (2005b) observed that, like presolar grains (Huss and Lewis, 1995), the matrix-normalized IOM abundances in the most primitive chondrites are similar. Thus, the matrix-normalization makes it possible to compare the different meteorite classes and to look for trends that might be common to all.…”
Section: Intra-and Inter-class Variationsmentioning
confidence: 88%
“…Despite this, there is considerable similarity between the most primitive IOM from chondrites and that in IDPs (Flynn et al, 2003;Busemann et al, 2006). It is possible, that all chondrites accreted the same primitive IOM component (Alexander et al, 1998;Alexander, 2005b). In this case, all variations in the functional group chemistry, and elemental and isotopic compositions must be consistent with evolution from a common precursor that was presumably synthesized in the outer Solar System or in the ISM.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Chondrule fragments are one of the main components of the matrix in chondritic meteorites (Brearley 1996;Alexander 2005) demonstrating that not all chondrules survived the collisions they experienced, whether they were during a chondrule formation event or not. While some of these fragments may result from collisions between the meteorite parent body and some impactor, some chondrule fragments have fine-grained rims similar to whole chondrules which may have been accreted as the core object moved through the solar nebula gas (Metzler et al 1992;Cuzzi 2004).…”
Section: Discussionmentioning
confidence: 99%